In‐Depth Analysis of the Internal Energy Conversion of Nuclear Batteries and Radiation Degradation of Key Materials. Issue 12 (14th October 2020) - Jiang, Tongxin; Xu, Zhiheng; Meng, Caifeng; Liu, Yunpeng; Tang, Xiaobin
Abstract : Low conversion efficiency and energy output are the main factors hindering the application of the radioluminescent nuclear battery in space. This study analyzes the energy conversion process and proposes a solution of performance promotion. It is found that the energy conversion efficiency of the photovoltaic units is enhanced with increasing incident light intensity. The efficiency of the AlGaInP unit is stable at 22% when the incident energy is at least 3 μW. As for the GaAs unit, the incident threshold value of the photovoltaic response sensitivity is greater than 120 μW. The overall efficiency of the radioluminescent nuclear battery is only 0.37%, consisting of an AlGaInP unit loaded with a low activity 63 Ni and the ZnS:Cu phosphor layer. The efficiency increases to 0.87% when an electron radiation source with 270.27 mCi cm −2 is adopted. Moreover, the intense intensity source constitutes an extremely electromagnetic pulse radiation environment, which cause the batteries to fail. The radiation damage is introduced to the phosphor layer by radiation sources, producing agglomerations and cracks on the surface and resulting in the transmittance reduction. This study provides guidance for improving the electrical property and optimization solutions of radioluminescent nuclear battery. Abstract : This work focuses on enhancement to the conversion efficiency of the radioluminescent nuclear battery. The internal energy conversion process is explored, discovering the incident energy threshold effect of the photovoltaic unit, and the solution to increase efficiency using intense radiation sources is proposed. Finally, the radiation degradation of phosphor layer caused by radiation is analyzed.